PROFIL GURU PAMONG MAHASISWA PROGRAM PENGALAMAN LAPANGAN KEPENDIDIKAN PROGRAM STUDI SOSIOLOGI STKIP PGRI SUMATERA BARAT - Saril, Nila - (Pendidikan Sosiologi, 2014)
Education Field Experience Program (PPLKK) PGRI STKIP Sociology courses in West Sumatera. This study aims to 1) Describe Background PPLKKK sociology teacher tutors in Padang, 2) to describe teachersâ understanding of the concepts of sociology tutor PPLKKK and 3) Describe the teacher mentoring student tutors sociology of PPLKKK. This research uses a qualitative approach and descriptive. The informant is Professor of Sociology Department of Civil Service Students PPLKKK collected through interviews, observation and documentation. Data analysis was done through data collection, data reduction, data presentation and conclusion. The results of this study indicate that: 1) Background PPLKKK sociology teacher tutors in Private SMA Padang is 8 teachers who have a background in education to teachers and only one person who is not a background of non education 2) understanding of the concept of teacher tutors sociology PPLKKK the SMA private Padang is good, because teachers can tutor students understand the capabilities dibuuhkan during follow PPLKKK and 3) mentoring Mentors tutor teachers doing students PPLKKK Sociology Education courses in private school Padang generally have good coaching but still not entirely can coaching.